Recientes investigaciones en la síntesis sustentable de pirazolinas - Trilleras, Jorge; De-La-Ossa-Alían, José-José; Pérez-Gamboa, Alfredo (Revista Científica, 2022)
In medicinal chemistry, extensive research efforts are continuously directed towards the discovery of new heterocycles with appropriate pharmacological effects. Specifically, the role of pyrazole derivatives in medical chemistry is vital, given its wide range of biological activities. In light of this notable observation, this review is carried out with a focus on advances in eco-friendly synthetic procedures in terms of performance, short reaction time, and clean conditions when obtaining 2-pyrazolines, based on a bibliographic analysis of research that takes the years 2019 to 2021 as a reference with regard to obtaining these systems in simplified and energy-sustainable conditions.